Overexpressing mouse model demonstrates the protective role of Muc5ac in the lungs - Ehre, Camille (National Academy of Sciences, 2012)
MUC5AC, a major gel-forming mucin expressed in the lungs, is secreted at increased rates in response to infectious agents, implying that mucins exert a protective role against inhaled pathogens. However, epidemiological and pathological studies suggest that excessive mucin secretion causes airways obstruction and inflammation. To determine whether increased MUC5AC secretion alone produces airway obstruction and/or inflammation, we generated a mouse model overexpressing Muc5ac mRNA ∼20-fold in the lungs, using the rCCSP promoter. The Muc5ac cDNA was cloned from mouse lungs and tagged internally with GFP. Bronchoalveolar lavage fluid (BALF) analysis demonstrated an approximate 18-fold increase in Muc5ac protein, which formed high-molecular-weight polymers. Histopathological studies and cell counts revealed no airway mucus obstruction or inflammation in the lungs of Muc5ac-transgenic (Muc5ac-Tg) mice. Mucus clearance was preserved, implying that the excess Muc5ac secretion produced an “expanded” rather than more concentrated mucus layer, a prediction confirmed by electron microscopy. To test whether the larger mucus barrier conferred increased protection against pathogens, Muc5ac-Tg animals were challenged with PR8/H1N1 influenza viruses and showed significant decreases in infection and neutrophilic responses. Plaque assay experiments demonstrated that Muc5ac-Tg BALF and purified Muc5ac reduced infection, likely via binding to α2,3-linked sialic acids, consistent with influenza protection in vivo. In conclusion, the normal mucus transport and absence of a pulmonary phenotype in Muc5ac-Tg mice suggests that mucin hypersecretion alone is not sufficient to trigger luminal mucus plugging or airways inflammation/goblet cell hyperplasia. In contrast, increased Muc5ac secretion appears to exhibit a protective role against influenza infection.